pocketbook; foreign speakers; Indonesian language; culture - Ulya Fawaida; Sudarmin Sudarmin; Sigit Saptono; Saiful Ridlo (Universitas Negeri Semarang, 2023)
Study this aim to analyze the ability to think creatively with the use of Microsains KIT on the madrasah program. A draft study this using